Realization and most often occupied positions and professions of graduates of communication and computer engineering and informatics and computer science professional fields - Stefanova, Tereza (Yearbook Telecommunications, 2024)
The specialists working in the ICT sector have mostly graduated from the professional fields of Communication and Computer Engineering and Informatics and Computer Science. Students from these two professional fields are educated in a total of 33 higher schools: 17 in Communication and Computer Engineering and 16 in Informatics and Computer Sciences. The article presents information on higher education institutions in both professional fields according to the "Taxable income of graduates" indicator. Data from the Rating System of Higher Education Institutions in Bulgaria in 2022 were used. The most often held positions and professions by graduates of the professional fields of Communication and Computer Engineering and Informatics and Computer Science are shown. Conclusions have been made about the changes in the incomes of the graduates of the two professional fields.